(untitled) - Holtz, Herman (Hoboken, N.J., 2004)
No matter what your field of expertise, this book will help you win clients through a variety of practical, proven techniques you'll find only here. Packed with real-world, effective business-driving tactics-as well as up-to-the-minute advice on getting the most out of new technologies-this helpful guide will show you how to market yourself in new ways, soar over IRS hurdles, and grow your home-office operation into a thriving practice.
Keywords: Business consultants,Management,Tư vấn kinh tế,Quản trị; Consultancy,Tư vấn